Identity Construction of Generation Z Foodie Nano-Influencers as a Personal Branding Strategy - Angela Gaya Noviko; Maylanny Christin (Eduvest - Journal of Universal Studies, 2026)
This research aims to explore the phenomenon of the influencer profession as a strategic solution for Generation Z in dealing with the high unemployment rate through the use of the digital creative economy. The main focus of this study is to analyze how foodie nano-influencers from Generation Z construct their identities as an instrument to strengthen personal branding on social media. Using a qualitative approach, this study applied Stuart Hall's identity construction theory which views identity as a dynamic process of "becoming", as well as Peter Montoya's personal branding theory to dissect self-image strategies. The results show that the identity construction of these nano-influencers is flexible (dynamic identity), where they adaptively adjust communication styles and content based on audience preferences and directives from brand partners. The personal branding strategy applied includes eight main laws (The Eight Laws of Personal Branding), namely Specialization (The Law of Specialization), Leadership (The Law of Leadership), Personality (The Law of Personality), Difference (The Law of Distinctiveness), Consistency (The Law of Visibility), Unity (The Law of Unity), Steadfastness (The Law of Persistence), and Good Name (The Law of Goodwill). These findings confirm that digital identity is not just a self-representation, but a planned strategy to build credibility and unlock economic opportunities amid fierce competition in the digital industry.